Prenatal diagnosis of midgut volvulus by fetal MRI: a retrospective study - Kou, Chenguang; Song, Yanfang; Gao, Duo; Zhou, Lixia (Frontiers in Pediatrics, 2024)
Background Fetal midgut volvulus is a rare disease, with a high risk of potentially life-threatening fetal complications. Purpose The aim of this study was to retrospectively analyze the imaging findings of fetal midgut volvulus diagnosed by magnetic resonance imaging (MRI) and explore its value in non-invasive prenatal diagnosis. Methods A retrospective collection of data from 156 fetuses suspected of intestinal obstruction by ultrasound examination in our hospital was conducted. All ultrasound examinations showed fetal intestinal dilation and fetal MRI diagnosis suspected midgut volvulus in 32 cases (32/156), of which 18 cases (18/32) that underwent surgical treatment in the neonatal period were confirmed to have midgut volvulus. MRI signs in the 18 fetuses with midgut volvulus were analyzed. Results During MRI examination, all 18 fetuses showed gastric and/or intestinal dilatation, most of which showed different degrees of obstruction in T1-weighted images (WIs) and T2WIs, showing the “black and white sign” (14/18), “whirlpool sign” (10/18), and “coffee bean sign” (6/18). High signal intensity changes in diffusion-weighted imaging sequences were observed in intestinal tubes with ischemia and infarction. Direct signs of vascular torsion were observed in some cases (8/18). MRI signs indicated fetal midgut volvulus with hydramnios (16/18), meconium pseudocyst (7/18), meconium peritonitis (4/18), testicular hydrocele (3/18), and secondary pulmonary dysplasia (6/18). Operations confirmed the diagnosis of segmental midgut volvulus in 15 cases, complete midgut volvulus in 3 cases, and combined with intestinal atresia in 8 cases. Conclusion Prenatal MRI plays an important role in the diagnosis of fetal midgut volvulus and the discovery of its complications, which can guide the treatment after birth and provide a reference for the prognosis.